عصر حاضرمیں طلبہ کی تربیت کا اسلوب: اسوہ رسول ﷺ کی روشنی میں: Students’ Training and character building style in modern era In the light of life of holy Prophetﷺ - Ahmad Qazi, Dr. Munir; Zia Ullah, Dr. Muhammad (Al-Amīr Research Journal for Islamic Studies, 2024)
Allah almighty has sent the holy prophet Muhammad ﷺ as a perfect teacher for a universal, educational and social revolution in the world. To achieve this lofty goal, the holy prophet made Dar-e- Arqam the first seminary and established a seminary named Suffa in Masjid Nabavi after the migration to Madinah. There He built a nation which changed the history of the world. Today the main reason for the continuous decline of the people of Muslim society in general and the people of Pakistani society in particular is the lack of guidance from the Prophetﷺ. Unfortunately, in teaching and character building of young students in our institutions the Prophetic method of training is being completely ignored. It is imperative that their ideology and character be developed in the light of the principles of Quran and Sunnah of the Holy Prophetﷺ.This article sheds light on the importance of building ideology and character of young students according to the Seerah of holy prophet Muhammadﷺ. The results have been compiled in an analytical manner with special reference to the life of holy prophet. Keywords: education, character building, purification, training style, ethics, ideology.